1989
DOI: 10.1103/physrevb.39.347
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural properties ofYBa2Cu3O

Abstract: YBazCu30z -F&, y 0.08 to 1.11, has been prepared by annealing YBazCu30z "(1:2:3)in NF3 gas. X-ray and neutron-diffraction studies show that the fluorine is structurally incorporated into the CuO chains, in the normally vacant O(5) sites along the a axis. Structurally, this results in a decrease in the orthorhombic strain (h -a)l(b+a). This material exhibits significant increases in diamagnetic expulsion and exclusion as a function of fluorine content, but no increase in T,. At sufficiently long anneal times (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Chlorine and bromine, on the other hand, would only enter the vacancies inside the chains. This is in accordance with structural data from PND [597,602].…”
Section: Halogenssupporting
confidence: 92%
See 2 more Smart Citations
“…Chlorine and bromine, on the other hand, would only enter the vacancies inside the chains. This is in accordance with structural data from PND [597,602].…”
Section: Halogenssupporting
confidence: 92%
“…It is experimentally well established that fluorine [597,600,601], chlorine and even bromine [602] enter the vacant oxygen sites in the Cu(1) coordination sphere, in concentrations decreasing in the said order. Quantum-chemical calculation [602] of the alternative structures for the thus formed halogenide cuprate anions show that upon the reaction with the molecular halogens only the vacant oxygen sites are reasonable candidates for accommodation of the halogen atoms.…”
Section: Halogensmentioning
confidence: 97%
See 1 more Smart Citation
“…After an annealing at 300 • C, these authors only observed an increase of the transition width when the fluorine content was increased. In the same conditions, LaGraff et al [12] did not observe any effect on T c but an increase of the diamagnetic expulsion and exclusion.…”
Section: Introductionmentioning
confidence: 79%
“…As Au is added to the Y 1 Ba 2 Cu 3± ±3x Au 3x O 7± ±d superconductor, the width of the superconductivity transition increases as a result of the formation of a nonuniform superconductivity phase. The T c , the volume fraction (± ±4pc DS ), and the Meissner effect (c ME /c DS ) for Y 1 Ba 2 Cu 3± ±3x Au 3x O 7± ±d at 10 K for various Au mole fractions are summarized in Table 2 [17]. The magnetization (M) is calculated from the ZFC in Fig.…”
Section: Resultsmentioning
confidence: 99%